Carbon monoxide-oxidising Pseudomonadota on volcanic deposits - Robin A. Dawson; Nicola Fantom; Tamara Martin-Pozas; Patricia Aguila; Gary M. King; Marcela Hernández (Environmental Microbiome)
Abstract Carbon monoxide (CO) oxidising microorganisms are present in volcanic deposits throughout succession, with levels of vegetation and soil influencing the communities present. Carboxydovores are a subset of CO oxidisers that use CO as an energy source, which raises questions about the physiological and metabolic features that make them more competitive in harsh volcanic ecosystems. To address these questions, samples were taken from volcanic strata formed by eruptions from Calbuco Volcano (Chile) in 2015 (tephra) and 1917 (soil). Two carboxydovore members of the Burkholderiaceae family were isolated for further study to elucidate the benefits of carboxydovory for the survival of these strains in extreme volcanic ecosystems. The isolates were identified as Paraburkholderia terrae COX (isolated from the 2015 tephra) and Cupriavidus str. CV2 (isolated from the 1917 soil). 16S rRNA gene sequencing showed that within the family Burkholderiacea, the genus Paraburkholderia dominated the 2015 volcanic deposit with an average relative abundance of 73.81%, whereas in the 1917 volcanic deposit, Cupriavidus accounted for 33.64% (average relative abundance). Both strains oxidise CO across a broad range of concentrations (< 100 ppmv – 10,000 ppmv), and genome sequence analysis revealed a candidate form-I carbon monoxide dehydrogenase (CODH), which is likely to catalyse this process. Each strain oxidised CO specifically at stationary phase but the conditions for induction of CODH expression were distinct. Cupriavidus strain CV2 expressed CODH only when CO was added to cultures (100 ppm), while Pb. terrae COX expressed CODH regardless of supplementary CO addition. Based on comparative metabolic and phylogenetic analyses, Cupriavidus strain CV2 is proposed as a novel species within the genus Cupriavidus with the name Cupriavidus ulmosensis sp. nov. for the type strain CV2T (= NCIMB 15506 T, = CECT 30956 T). This study provides valuable insights into the physiology and metabolism of carboxydovores which colonise volcanic ecosystems.